Boston Confronts Jim Crow, 1890-1920 - Schneider, Mark R. (Northeastern University Press, 2019)
Boston, the headquarters of radical abolition during the antebellum period, is, paradoxically, often thought of as unfriendly to African-Americans today. In this study of the city's significant role in the fight against racism between 1890 and 1920, Mark Robert Schneider illuminates the vital links between Boston's antislavery tradition, race reform at the turn of the century, and the modern civil rights movement. Originally published by Northeastern University Press in 1997. With a new foreword by Zebulon Vance Miletsky.